EXPLORATION OF BOROBUDUR TEMPLE PANELS IN TRADIGITAL VISUAL LANGUAGE: CONSERVATION INNOVATION THROUGH AUDIOVISUAL TECHNOLOGY - Yayat, Yayat; Anak Agung Gede Rai Remawa (International Journal of Social Science, 2024)
Borobudur Temple, an ancient architectural marvel located in Central Java, Indonesia, stands as one of the world’s most significant cultural heritage sites. Constructed during the 8th century by the Sailendra dynasty, Borobudur is an extraordinary representation of Mahayana Buddhist teachings, conveyed through its intricate narrative reliefs. As modern technology advances, methods for preserving and presenting this cultural legacy are evolving. This paper investigates the integration of visual effects (VFX) and audiovisual media in enhancing the understanding of the temple's relief panels. By employing advanced VFX techniques, the narrative stories embedded in the temple’s stone reliefs are reconstructed in ways that offer visitors a deeper, more immersive visual experience. The incorporation of technology not only aids in preserving the cultural history of Borobudur but also facilitates educational outreach by introducing the temple to global audiences through an interactive digital medium. This study contributes to the field of digital art conservation and cultural heritage preservation